Sex differences in inflammatory cytokine production in hepatic ischemia-reperfusion - He Jun; Dowlatshahi Shadi; Spielman William; Crockett Elahé T (BMC, 2006)
Abstract Background The inflammatory response to hepatic ischemia-reperfusion (I/R) is associated with an increase in cytokine production. Studies have documented that sex hormones modulate both the innate and adaptive immune responses, and that females are more robust than males. The aim of this study was to determine whether a sex difference in cytokine response to hepatic I/R exists under normal pathophysiologic condition without hormone intervention. Methods Adult C57BL/6 mice underwent 90 min of hepatic ischemia followed by various reperfusion periods (0, 1.5, 3, 6 hr). Plasma cytokine TNF-α, IL-6, MIP-2, and KC were measured. Liver injury was assessed by plasma alanine transaminase (ALT) levels and liver histopathology. Results A reperfusion time-dependent increase in hepatocellular injury was observed in both males and females, as indicated by increasing levels of plasma ALT and liver histopathology. The plasma cytokines were significantly increased in both female and male I/R groups compared to their respective sham counterparts. However, there was a significant difference in cytokine kinetics between the female and male I/R groups. Female mice initially had a higher level of IL-6, KC, and MIP-2 in response to I/R, which began to decline after 3 hr of reperfusion and were significantly lower than the male I/R counterparts by 6 hr of reperfusion. In contrast, the hepatocellular injury and TNF production were only moderately lower in female IR than male IR. Conclusion The study underscores role of the gender in differential inflammatory cytokine expression in response to hepatic I/R, which may reflect the host response outcome.